Risk Mitigation Strategy for Problematic Mortgage Financing at Bank BTN Syariah KCPS Probolinggo 2020-2023 - Hilda Zamrotul Firdausiah (Universitas Nurul Jadid, 2024)
Home ownership credit (KPR) financing is one of the mainstay products offered by financial institutions to meet the needs of the community for housing. However, the increase in the number of problematic KPR financing can bring significant risks to banks and financial institutions. This study aims to identify and evaluate effective risk mitigation strategies in dealing with problematic KPR financing. The research methods used include literature studies and interviews with practitioners in the banking sector. The results of the study indicate that risk mitigation strategies can be grouped into several categories, such as stricter credit analysis, increased communication with customers, application of technology for risk monitoring, and development of restructuring programs for customers who experience payment constraints. In addition, customer education regarding financial management and the importance of planning before taking a KPR has also proven effective in reducing risk. This study is expected to provide input for financial institutions in formulating better policies and strategies to face the challenges of problematic KPR financing, as well as supporting the sustainability and stability of the banking sector as a whole.